Uji Daya Lekat Mukoadhesif secara In Vitro beberapa Eksipien Polimer Tunggal dan Kombinasinya pada Lambung dan Usus Tikus - Teti Indrawati; Goeswin Agoes; Elin Yulinah; Yeyet Cahyati Sumirtapura (Jurnal Matematika & Sains, 2005)
Mucoadhesive strength test of some polymer excipients is importance for development of oral sustain release with mucoadhesive system to enchance bioavailability. Mucoadhesive strength of granules that prepared using single and combination of polymers i.e. from carboxymethylcellulose, gum arabic, and sodium alginate with Metolose 90SH-15.000 (Metolose K-15) and Metolose 90SH-100.000 (Metolose K-100) on rat stomach and intestinal had been determined by bioadhesion and wash off test. Results showed that single polymer and its combination could adhesive to rat stomach and intestine in 5 minuter. The granul prepared using Metolose K-15 and sodium alginat in single and combination form gave the strongest adhesive strength to stomach, while Metolose K-15 and gum arabic in a single form showed the strongest adhesive to intestine. The strongest adhesion to stomach and intestine was the granule combination of sodium alginat and Metolose K-15 (20 : 40) with the amount of granule adhesived to stomach and intestine was 100 % and 88 % respectively.